2016
DOI: 10.1007/s00261-015-0618-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute pyelonephritis in transplanted kidneys: can diffusion-weighted magnetic resonance imaging be useful for diagnosis and follow-up?

Abstract: Purpose: To assess reliability of diffusion-weighted magnetic resonance imaging (DW-MRI) in the management of acute pyelonephritis (APN) foci in transplanted kidneys. Materials and methods: In the 2012-2014 period, 24 kidney-transplanted patients underwent MR screening for clinical suspicion of APN. Two readers independently analyzed all images, establishing presence and location of APN foci. The 22 patients who were positive at the MR exam constituted the study population. For each patient the apparent diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In particular, tracer accumulation in parts of the renal pelvis may be easily differentiated from cortical uptake using T2weighted MR sequences. Diffusion-weighted MRI has high sensitivity to detect areas of restricted diffusion in renal parenchyma indicating pyelonephritis (15). In particular, MRI facilitates the discrimination of foci with leukocyte infiltration from normal parenchyma because the range of ADC values in normal parenchyma is narrow and, in contrast to SUVs, there is no overlap for ADC min and only little overlap for ADC mean between foci and parenchyma ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, tracer accumulation in parts of the renal pelvis may be easily differentiated from cortical uptake using T2weighted MR sequences. Diffusion-weighted MRI has high sensitivity to detect areas of restricted diffusion in renal parenchyma indicating pyelonephritis (15). In particular, MRI facilitates the discrimination of foci with leukocyte infiltration from normal parenchyma because the range of ADC values in normal parenchyma is narrow and, in contrast to SUVs, there is no overlap for ADC min and only little overlap for ADC mean between foci and parenchyma ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-pentixafor has also been reported to specifically identify postinfarction myocardial inflammation mediated by CXCR4 1 leukocytes (13) and atherosclerotic plaque inflammation (14). Diffusion-weighted MRI has been shown to provide useful information for diagnosing and monitoring pyelonephritis foci in transplanted kidneys (15). MRI-derived apparent diffusion coefficients (ADCs) are inversely correlated with inflammatory cell infiltration in the kidneys (16).…”
mentioning
confidence: 99%
“…Areas without any signal abnormalities were considered to be healthy renal tissue. In the acute phase, ADC difference was significant between affected and unaffected tissue and showed excellent discriminatory ability [85]. Other studies confirm the ability of DWI and DTI to detect renal infection in kidneys and diffusion parameters could play an important role in monitoring treatment effectiveness [85][86][87][88].…”
Section: Diffusion Biomarkersmentioning
confidence: 87%
“…Vivier et al [21] found DWI and contrast-enhanced MRI to be of equivalent value in a study of pediatric patients. Several studies in adults have shown DWI to be useful in diagnosing uncomplicated pyelonephritis [19,[22][23][24]. One study by Rathod et al [19] found a higher sensitivity of DWI (95%) compared with noncontrast CT (67%) and contrast-enhanced CT (88%) in the diagnosis of pyelonephritis.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%